Answer:
2x+4=4x-10
Step-by-step explanation:
AOB and COD are same
The first thing we are going to do to find (g°f)(3), is find (g°f)(x). To do that, we are going to evaluate g(x) at f(x):
(g°f)(x)=
![g(f(x))=g(3x-2)=(3x-2)^2=9x^2-12x+4](https://tex.z-dn.net/?f=g%28f%28x%29%29%3Dg%283x-2%29%3D%283x-2%29%5E2%3D9x%5E2-12x%2B4)
Now, we can evaluate (g°f) at 3:
![g(f(3))=9(3)^2-12(3)+4](https://tex.z-dn.net/?f=g%28f%283%29%29%3D9%283%29%5E2-12%283%29%2B4)
![g(f(3))=9(9)-36+4](https://tex.z-dn.net/?f=g%28f%283%29%29%3D9%289%29-36%2B4)
![g(f(3))=81-32](https://tex.z-dn.net/?f=g%28f%283%29%29%3D81-32)
![g(f(3))=49](https://tex.z-dn.net/?f=g%28f%283%29%29%3D49)
We can conclude that the correct answer is
c. 49
6 times
6 * 1/4 is 6/4
6/4 is 1 2/4 which is 1 1/2
True
Note that:
![secant \theta = \frac{1}{cos\theta}](https://tex.z-dn.net/?f=secant%20%5Ctheta%20%3D%20%5Cfrac%7B1%7D%7Bcos%5Ctheta%7D)
The graph of sine and cosine functions are very similar. They only have a shift in the x -axis.
That is, sin x = cos (90 - x)
Since there is a great similarity between the sine and cosine graphs, and the secant graph is an inverse of the cosine graph, the graph of sine can be used to construct the graph of the secant function
Mathematically:
since sec x = 1 / cos x
and, cos x = sin (90 - x)
therefore, sec x = 1 / sin (90 - x)
The graphs of the sine and secant functions are attached to this solution
Learn more here: brainly.com/question/9554579